The Myth of the Outlaw in Mexican and North American Border Music - Kennedy, Victor (Music with a Message: Words, Music and Propaganda 2, 2025)
Many songs embody myths that create social and cultural identity. One example is the Myth of the Outlaw, which was instrumental in the construction of American society in frontier days; its misappropriation and misuse, however, threaten to deconstruct and divide that society in our time. A current issue in political discourse is the question of immigration and identity, and the Myth of the Outlaw is at the heart of it. This chapter will show how this myth is used in folk and popular music, and how this music is used in turn for political propaganda.